Forced convection by Inclined Rotary Bridgman method for growth of CoSb3 and FeSb2 single crystals from Sb-rich solutions - Pillaca, M (2017)
The authors are grateful to the former LMU students Tamara Maletin and Viviane Cocivera for their valuable contributions in the preliminary experiments to this study, to Stefanie Hoser for surface polishing of the samples and to SoHyun Park for her assistance in Rietveld refinement. This work has been partly conducted within the European integrated Center for the development of new Metallic Alloys and Compounds. M.P. is grateful for funding by the Peruvian Council of Science and Technology (CONCYTEC), grant no. 221-2014-FONDECYT.